DIE ONTSTAAN EN ONTWIKKELING VAN DIE KWARTIERMEESTER-GENERAAL - Bredenkamp, J.D. (Scientia Militaria - South African Journal of Military Studies, 2012)
The origin and development of QMG from 1912, through the First World War and the Second World War is discussed with special emphasis on the changes that evolved and occurrences, people and factors that contributed to bring about the organisation as we know it today.